Legal Regulations for Victims and Perpetrators of Psychological Violence by the Bitung Police Department - Bawole, Herlyanty Y. A.; Karwur, Grace M. F.; Bawole, Grace Y. (Research Horizon, 2025)
Psychological violence is a form of non-physical harm that causes serious mental suffering and requires strong legal protection within a just and recovery-oriented criminal justice system. This research aims to examine how legal protection is provided by the Police to victims of psychological violence crimes. Using a library research method, the study analyzes literature, legislation, and other written legal materials related to victim protection. The findings indicate that legal protection for victims of psychological violence is a state obligation implemented through law enforcement agencies, including the police, prosecutors, and courts, and covers legal, psychological, and social aspects. In Indonesia, psychological violence has been legally recognized as a criminal act, particularly in the domestic sphere under Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and is further reinforced by Law Number 13 of 2006 as amended by Law Number 31 of 2014. In conclusion, police-provided legal protection is essential not only to guarantee victims’ rights during the legal process but also to ensure state recognition of the suffering experienced by victims of psychological violence.